Impact of aspirin on takotsubo syndrome: a propensity score-based analysis of the InterTAK Registry - D'Ascenzo, Fabrizio; Gili, Sebastiano; Bertaina, Maurizio; Iannaccone, Mario; Cammann, Victoria Lucia; Di Vece, Davide; Kato, Ken; Saglietto, Andrea; Szawan, Konrad A.; Frangieh, Antonio H.; Boffini, Beatrice; Annaratone, Margherita; et al. (European journal of heart failure, 2020)
Aims The aim of the present study was to investigate the impact of aspirin on prognosis in takotsubo syndrome (TTS). Methods and results Patients from the International Takotsubo (InterTAK) Registry were categorized into two groups based on aspirin prescription at discharge. A comparison of clinical outcomes between groups was performed using an adjusted analysis with propensity score (PS) stratification; results from the unadjusted analysis were also reported to note the effect of the PS adjustment. Major adverse cardiac and cerebrovascular events (MACCE: a composite of death, myocardial infarction, TTS recurrence, stroke or transient ischaemic attack) were assessed at 30-day and 5-year follow-up. A total of 1533 TTS patients with known status regarding aspirin prescription at discharge were included. According to the adjusted analysis based on PS stratification, aspirin was not associated with a lower hazard of MACCE at 30-day [hazard ratio (HR) 1.24, 95% confidence interval (CI) 0.50-3.04, P = 0.64] or 5-year follow-up (HR 1.11, 95% CI 0.78-1.58, P = 0.58). These results were confirmed by sensitivity analyses performed with alternative PS-based methods, i.e. covariate adjustment and inverse probability of treatment weighting. Conclusion In the present study, no association was found between aspirin use in TTS patients and a reduced risk of MACCE at 30-day and 5-year follow-up. These findings should be confirmed in adequately powered randomized controlled trials. ClinicalTrials.gov Identifier: NCT01947621.